Hydrometeorological Disasters Caused by Forgotten Local Wisdom (A Study of Local Wisdom ' Pilot' of the Gayo Community in Forest Conservation) - Linge, Abdiansyah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
The hydrometeorological disaster in Aceh caused floods and landslides, causing numerous casualties and significant economic losses. The hydrometeorological disaster was exacerbated by the deterioration of forests in the highlands. Forest destruction is caused by many factors, one of which is the decline of local wisdom values related to forest exploitation.The norms and values of the Gayo highland community are closely linked to the interaction between nature and humans. Communities living alongside forests or in highland areas are the primary bulwark in maintaining forest sustainability. The community's role in forest preservation is to convey values or ideas that live within the community, referred to as local wisdom. This study focuses on the local wisdom of " rintis " (the "root") within the Gayo ethnic group. This research will construct the values contained in the pioneering norms as ideas or concepts in the interaction between humans and nature.The methodology used in this research is a qualitative approach with a micro-ethnography approach, reconstructing the implementation of nature/forest conservation values within the local wisdom or customary system of the Gayo community through the pioneer norms. Starting from describing norms to actualizing norms in life so that they have benefits for environmental sustainability.This research concludes that the values of the rintis norm have been forgotten in Gayo life due to the need to fulfill economic needs, resulting in areas prohibited by custom being converted into agricultural and plantation land. Therefore, the initial norm as local wisdom remains limited to imagination and is not applied in the interaction between humans and nature.